Odpowiedzi

Najlepsza Odpowiedź!
2009-09-27T09:39:14+02:00
A) licz. 6a+7 w mian. 7 i to wszystko -3 = licz. 5a-3 mian. 8 /×56
48a + 56 - 168 = 35a - 21
48a - 112 = 35a - 21 /+112-35a
13a = 91 /:13
a = 7
b) licznik b-4 mianownik 5 = 9- licznik 2b-41 mianownik 9 /×45
9b-36 = 610-10b /+36+10b
19b = 646 /:19
b = 34
pozdrawiam :)
  • Użytkownik Zadane
2009-09-27T09:39:26+02:00
A)
(6a+7/7)-3=(5a-3/8) //*56
6(6a+7)=7(5a-3)
36a+42=35a-21
36a-35a=-21-42
a=-63

b )
(b-4/5)=9-(2b-41/9) //*45
9(b-4)=-405-5(2b-41)
9b-36=-405-10b-205
9b+10b=-610+36
19b=574
b=30 i 4/19